2018
DOI: 10.1002/jrs.5541
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy analysis of new copper‐cysteamine photosensitizer

Abstract: Raman spectroscopy and several microstructure analysis techniques have been used to better characterize recently synthesized copper‐cysteamine Cu3Cl(SR)2, where R = CH2CH2NH2. Nanoparticles of this new copper‐cysteamine have been identified as having potential applications in radiation detection and cancer treatment because of the fact that they can be activated by light, X‐rays, ultrasound, and microwave radiation to produce reactive oxygen species. Three samples were grown under different conditions, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…We further measured the FTIR spectra and XRD patterns of Cu-Cy before and after the Fenton-like reaction (Figure C and D). As shown in Figure C, the FTIR spectra of Cu-Cy matched with previously reported results . The peaks at 3300 cm –1 , 2800 cm –1 , and 1600 cm –1 correspond to NH 2 stretching, CH 2 stretching, and N–H bending, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We further measured the FTIR spectra and XRD patterns of Cu-Cy before and after the Fenton-like reaction (Figure C and D). As shown in Figure C, the FTIR spectra of Cu-Cy matched with previously reported results . The peaks at 3300 cm –1 , 2800 cm –1 , and 1600 cm –1 correspond to NH 2 stretching, CH 2 stretching, and N–H bending, respectively.…”
Section: Resultssupporting
confidence: 89%
“…As shown in Figure 3C, the FTIR spectra of Cu-Cy matched with previously reported results. 47 The peaks at 3300 cm −1 , 2800 cm −1 , and 1600 cm −1 correspond to NH 2 stretching, CH 2 stretching, and N−H bending, respectively. Additionally, the peaks that are in the range of 700−1300 cm −1 correspond to C−N and C−C−N vibrations.…”
Section: Stability Study During Fenton-like Reactionmentioning
confidence: 99%
“…Akafzade et al [ 92 ] reported Raman spectral analysis from nanoparticles of a new copper‐cysteamine photosensitizer. These nanoparticles have been identified as having potential applications in radiation detection and cancer treatment because of the fact that they can be activated by light, X‐rays, ultrasound, and microwave radiation to produce reactive oxygen species.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Raman spectroscopy is a type of molecular vibrational spectroscopy based on the Raman scattering effect. It has the advantages of simple sample preparation, in situ analysis, and nondestructive treatment of samples and has been widely used in geology, [37,38] material, [39,40] environmental, [41][42][43][44][45] and other fields. [46] Raman spectroscopy gives detailed information on the chemical structure and crystallinity of carbonaceous materials.…”
Section: Introductionmentioning
confidence: 99%